1998
DOI: 10.1074/jbc.273.40.25552
|View full text |Cite
|
Sign up to set email alerts
|

The Chaperone BiP/GRP78 Binds to Amyloid Precursor Protein and Decreases Aβ40 and Aβ42 Secretion

Abstract: Recent studies of cellular amyloid precursor protein (APP) metabolism demonstrate a ␤-/␥-secretase pathway resident to the endoplasmic reticulum (ER)/Golgi resulting in intracellular generation of soluble APP (APPs␤) and A␤42 peptide. Thus, these intracellular compartments may be key sites of amyloidogenic APP metabolism and Alzheimer's disease pathogenesis. We hypothesized that the ER chaperone immunoglobulin binding protein (BiP/GRP78) binds to and facilitates correct folding of nascent APP. Metabolic labeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
117
2
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(134 citation statements)
references
References 33 publications
8
117
2
7
Order By: Relevance
“…This suggests their participation in the folding and removal of the excessively synthesized A␤PP, and/or of its proteolytic product A␤. Although binding of calreticulin and BiP/ GRP78 to A␤PP has previously been reported in other systems, [27][28][29] our studies are the first to demonstrate that calnexin, GRP94, and ERp72 physically associate with A␤PP, which suggests an importance of ER chaperones in A␤PP folding.…”
Section: Upr In S-ibm Musclementioning
confidence: 66%
“…This suggests their participation in the folding and removal of the excessively synthesized A␤PP, and/or of its proteolytic product A␤. Although binding of calreticulin and BiP/ GRP78 to A␤PP has previously been reported in other systems, [27][28][29] our studies are the first to demonstrate that calnexin, GRP94, and ERp72 physically associate with A␤PP, which suggests an importance of ER chaperones in A␤PP folding.…”
Section: Upr In S-ibm Musclementioning
confidence: 66%
“…We showed that induction of GRP78 and CHOP by indomethacin was not specifically observed in gastric mucosal cells but observed in other cells, such as HEK293 (human embryonic kidney) cells (data not shown). Since GRP78 was shown to decrease amyloid b-protein production, 34 we propose that GRP78 induced by NSAIDs is involved in inhibition of amyloid b-protein production by NSAIDs and their anti-Alzheimer's disease activity.…”
Section: Discussionmentioning
confidence: 90%
“…Finally, inhibition of proteasomes would inhibit the degradation of misfolded proteins of the endoplasmic reticulum, leading to an increased demand on resident chaperones of this compartment (reviewed in ref. 32) and the possibility of increased amyloid precursor protein processing through competitive effects at the level of BiP͞Grp78 (33). Inhibition of 26S proteasomes thus might contribute to both A␤ and tau pathology.…”
Section: Discussionmentioning
confidence: 99%